Application of aloe vera gel edible coating for Minimizing damage to tomatoes in the farming group Usaha Bersama Pemuda Solok Saiyo Sakato, Nagari Surian, Solok Regency - Parbuntari, Hesty; Amelia, Kiki; Kurniawati, Desy; Mahmud, Mahmud; Martha, Rahma Dyan (Pelita Eksakta, 2024)
The most common profession among Surian people is in the agricultural sector, such as tomato farmers. The farmers who are partners in PKM activities are tomato farmers in Nagari Surian, Pantai Cermin District, Solok Regency. Tomato farmers often experience losses because when the tomato harvest season arrives the product is abundant, while demand is constant. Farmers will just let the tomatoes rot because the harvesting process will take up a lot of energy and money. This activity focuses on efforts to control the quality of post-harvest tomatoes by using a coating technique based on edible natural ingredients (edible coating) with the natural ingredient aloe vera. The stages of this activity are divided into three activities, namely initial activities which include analysis of partner needs, core (providing material and practice) and final (program evaluation). Based on the results of a questionnaire given to partners as many as 20 people with an age range of 25 – 46 years and consisting of men and women, 90% of participants agreed that this edible coating could be used to solve the problem of tomatoes that rot easily after harvest.